1990
DOI: 10.1016/s0889-8529(18)30337-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone Disease in Primary Hyperparathyroidism

Abstract: Bone disease in severe primary hyperparathyroidism (PHPT) is described classically as osteitis fibrosa cystica (OFC). Bone pain, skeletal deformities and pathological fractures are features of OFC. Bone mineral density is usually extremely low in OFC, but it is reversible after surgical cure. The signs and symptoms of severe bone disease include bone pain, pathologic fractures, proximal muscle weakness with hyperreflexia. Bone involvement is typically characterized as saltand-pepper appearance in the skull, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(42 citation statements)
references
References 29 publications
6
34
0
2
Order By: Relevance
“…In doing so, the osteoclasts create long furrows in the interior of the trabecular plate (Figure 29.12). 12,37,77,78 This mechanism is compatible with Eriksen's finding of decreased erosion depth. 48,49 Under conditions of moderate PTH excess, the change in osteoclast behavior would result in a more tangential pattern of "sweeping erosion," quantitatively translated by more shallow erosion lacunae, thereby allowing the plates to remain connected, although they are thinner than normal.…”
Section: Mechanism Of Maintenance Of Cancellous Bone Volume and Strucsupporting
confidence: 67%
See 1 more Smart Citation
“…In doing so, the osteoclasts create long furrows in the interior of the trabecular plate (Figure 29.12). 12,37,77,78 This mechanism is compatible with Eriksen's finding of decreased erosion depth. 48,49 Under conditions of moderate PTH excess, the change in osteoclast behavior would result in a more tangential pattern of "sweeping erosion," quantitatively translated by more shallow erosion lacunae, thereby allowing the plates to remain connected, although they are thinner than normal.…”
Section: Mechanism Of Maintenance Of Cancellous Bone Volume and Strucsupporting
confidence: 67%
“…37 Among histomorphometric studies performed over four decades ago, the classic studies of Jowsey, Meunier, Melsen, Mosekilde, and their colleagues contributed importantly to our present understanding of bone turnover in this disease. [38][39][40][41][42] More recent studies have confirmed the accelerated rate of bone remodeling in PHPT.…”
Section: Bone Turnover In Primary Hyperparathyroidismmentioning
confidence: 99%
“…The underlying mechanistic reason for the apparent uncoupling of bone formation to the increased bone resorption is unclear. Defective bone coupling has been implicated as a key contributing factor for bone loss in many metabolic bone diseases with excessive bone resorption, such as postmenopausal osteoporosis (28), hyperparathyroidism (29), hyperthyroidism (29), renal insufficiency (30), and osteodystrophies (31). It is conceivable that pathologic conditions with persistent activation of bone resorption (such as in the case of PTP-oc overexpression) could create a situation where a "disequilibrium" develops between resorption and the coupled bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…63 However, increased bone turnover and increased rate of loss of cortical bone are non-specific, whereas osteitis fibrosa is a qualitatively different bone disorder that is specific to excess PTH secretion, 57 and its presence is both a logical and an unambiguous index of a particular degree of disease severity that has existed for several years. Regrettably, many observers have failed to appreciate this crucial distinction and have reported the presence or absence of "bone disease" without qualification.…”
Section: Primary Hyperparathyroidism: Disease Course As An Expressionmentioning
confidence: 99%